2017
DOI: 10.11604/pamj.2017.28.84.11712
|View full text |Cite
|
Sign up to set email alerts
|

Place de la splénectomie dans la prise en charge de l’hypertension portale non cirrhotique: à propos de 3 cas

Abstract: L’hypertension portale non cirrhotique est une affection décrite pour la première fois par Guido BANTI en 1898 comme une affection associant une hypertension portale avec splénomégalie et anémie sur foie sain. Le diagnostic repose sur l’échographie abdominale, la splénoportographie et la biopsie hépatique. Le but de notre travail est d’évaluer la place de la splénectomie dans l’hypertension portale non cirrhotique à travers une étude rétrospective portant sur 3 malades dont 2 femmes et un homme pris en charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Thus, splenectomy might be justified in the management of noncirrhotic portal hypertension by correcting hypersplenism and thereby decreasing portal blood flow. 3 , 14 , 15 In contrast to cirrhosis, there is still no consensus regarding the prevention of hemorrhagic recurrence in patients with HSS because of the lack of sufficient literature data. However, studies have suggested a combination of surgical (splenectomy) and endoscopic methods to prevent recurrent bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, splenectomy might be justified in the management of noncirrhotic portal hypertension by correcting hypersplenism and thereby decreasing portal blood flow. 3 , 14 , 15 In contrast to cirrhosis, there is still no consensus regarding the prevention of hemorrhagic recurrence in patients with HSS because of the lack of sufficient literature data. However, studies have suggested a combination of surgical (splenectomy) and endoscopic methods to prevent recurrent bleeding.…”
Section: Discussionmentioning
confidence: 99%